Understanding the ZEB1 interactome during lymphangiogenesis - Ahmed, Nada (2025)
Endothelial cells (ECs) constitute the crucial lining of blood and lymphatic vessels, controlling vascular integrity and function. During quiescence, ECs regulate junctional integrity and barrier stability. Recently, ZEB1 was hypothesised to contribute to endothelial quiescence. Integrating mass spectrometric and transcriptomic analyses in lymphatic ECs uncovered that ZEB1 contributes to junctional reorganization. Silencing ZEB1 significantly reduced VE-cadherin phosphorylation at Y731 and Y685 (59%±5.39, 71%±15,p<0.05, respectively), consequently compromising barrier integrity. Silencing ZEB1 downregulated YES and YAP1 suggesting that altered VE-cadherin signalling was a consequence of ZEB1 mediated-YES/YAP1 signalling. In LECs, silencing YAP1 induced cytoskeletal remodelling, and functionally compromised EC barrier phenocopying ZEB1 loss. Consistently, YAP1 loss showed dephosphorylation of Y685 and Y731.